DEVELOPING THE UNDERSTANDING OF SCIENTIFIC CONCEPT BASED ON THE ASPECT OF SCIENCE LITERACY FOR STUDENTS OF ELEMENTARY SCHOOL EDUCATION PROGRAM THROUGH THE APPLICATION OF PROJECT BASED LEARNING - Masfuah, Siti; Fakhriyah, Fina (Unnes Science Education Journal, 2017)
This research aims to: 1) know the better learning model in developing science concept comprehension in science application course, that is learning model of project-based learning or direct learning in ELEMENTARY SCHOOL EDUCATION PROGRAM student of 3rd semester on Science Application course and 2) to know the influence of student skill In making the media towards understanding the concept of science. This study uses quasi-experimental design. The population of this research is 3-semester students of ELEMENTARY SCHOOL EDUCATION PROGRAM UMK with the 3H class sample as experiment class and class of 3G as control class determined by random sampling. In the beginning, both classes were given pretest, then the PjBL learning treatment in the experimental class and direct learning in the control class. At the end of the meeting, the two classes are given posted for analyzed improvement and hypothesis testing. The hypothesis test is done by data analysis using an inferential statistic that starts with homogeneity test, normality test, gain test, t-test and simple linear regression test. Based on the data analysis, it is known that the average value of the conceptual understanding of the experimental class is better than the control class. In addition, based on gain test it is known that the improvement of understanding of the experimental class concept is 0,49 (medium), while control class increase equal to 0,29 (low). Furthermore, based on the regression test, the equation obtained Å¶ = 1.047 X - 4,36 and obtained the correlation coefficient between the skill of making the media with student concept understanding (rXY) of 0.42 which means there is a positive relationship between the skill of making the media with the understanding of student concept. In addition, based on data analysis, obtained the coefficient of determination (r2) of 0.18 which means that 18% understanding of concepts influenced by the skill of making media, while 82% influenced by other factors.